Designing Sustainable Agricultural Ecotourism Around Bali Cattle Husbandry: A Community Based Conservation Model for Sakti Village, Nusa Penida - Ni Made Ayu Gemuh Rasa Astiti; S Vongtanaboo; W Hancharoen; S Homya; Ida Bagus Komang Mahardika; I Kadek Merta Wijaya (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Sustainable agricultural ecotourism in small?island environments requires management systems that integrate animal welfare, conservation, and local livelihood goals. This study aims to design a practical, community?based model for agricultural ecotourism centred on Bali cattle husbandry in Sakti Village by linking welfare?oriented pen design, feeding management, and governance processes to broader ecological and cultural objectives. The research employed a design?science approach supported by spatial planning, participatory governance, and field?based assessments to develop siting standards, construction guidelines, operational protocols, and monitoring systems suited to island conditions. Results show that appropriate roofing, ventilation, pen dimensions, sanitation systems, and continuous water access significantly improved cattle comfort, biosecurity, and visitor safety, while balanced feeding strategies supported stable growth and resilience across seasons. Waste?to?resource practices strengthened circularity, and community involvement enhanced policy coherence, social acceptance, and long?term feasibility. These findings illustrate that well?designed husbandry standards can simultaneously improve animal welfare, enrich visitor interpretation, and support community benefits when embedded within adaptive governance. Overall, the study provides an integrated framework for developing livestock?based agricultural ecotourism on small islands and demonstrates its potential to align tourism development with conservation aims, cultural heritage, and rural prosperity. Contribution to Sustainable Development Goals (SDGs):SDG 8 (Decent Work and Economic Growth)SDG 11 (Sustainable Cities and Communities):SDG 12 (Responsible Consumption and Production)SDG 13 (Climate Action)SDG 15 (Life on Land)